2023
DOI: 10.1111/coep.12602
|View full text |Cite
|
Sign up to set email alerts
|

Mass gatherings contributed to early COVID‐19 mortality: Evidence from US sports

Abstract: Social distancing is important to slow the community spread of infectious disease, but it creates enormous economic and social cost. Thus, it is important to quantify the benefits of different measures. We study the ban of mass gatherings, an intervention with comparably low cost. We exploit exogenous spatial and temporal variation in NBA and NHL games -which arise due to the leagues' predetermined schedules -and the suspension of the 2019-20 seasons. This allows us to estimate the impact of indoor mass gather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 71 publications
2
20
0
Order By: Relevance
“…These empirical results are consistent with the recent evidence from the U.S. on positive relationship between mass-gathering sporting event and the spread of influenza and COVID-19 (Ahammer et al, 2020; Cardazzi et al, 2020; Stoecker et al, 2016). As large gatherings of people increase, the frequency of human contact and the probability of transmission increases (Stoecker et al, 2016).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
See 3 more Smart Citations
“…These empirical results are consistent with the recent evidence from the U.S. on positive relationship between mass-gathering sporting event and the spread of influenza and COVID-19 (Ahammer et al, 2020; Cardazzi et al, 2020; Stoecker et al, 2016). As large gatherings of people increase, the frequency of human contact and the probability of transmission increases (Stoecker et al, 2016).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 91%
“…The second set of studies, which began to receive attention following the global epidemic of COVID-19, analyzed the impact of professional sporting events on the spread of infectious diseases within local communities. Generally, these studies have found consistent results in which professional sport teams and events produce negative externalities in the form of increased respiratory disease spread and/or mortality rates, thus supporting the call for restrictions on all forms of MGs during the COVID-19 epidemic (Ahammer et al, 2020; Cardazzi et al, 2020; Olczak et al, 2020; Stoecker et al, 2016).…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Closer to our population of interest, that is, adults, are studies analyzing sports, social, and political gatherings. Large sporting events such as hockey, basketball, and football games can lead to higher COVID‐19 prevalence (Alexander et al., 2020; Breidenbach & Mitze, 2021; Carlin et al., 2021). Similarly, smaller gatherings such as birthdays or bar meetings increase the likelihood of subsequent infections (Harris, 2020; Whaley et al., 2021).…”
Section: Introductionmentioning
confidence: 99%